USE OF SURFACTANT WITH DIFFERENT VOLUMES OF FUNGICIDE APPLICATION IN SOYBEAN CULTURE - Roehrig,Rafael (2018)
ABSTRACT Application volume, adjuvants that act on the drop surface tension and droplet spectrum are the main factors affecting leaf surface coverage and the spray penetration droplets inside the canopy of the soybean crop, which may have an impact on fungicide efficiency, since those used in the handling of Asian-rust, including those that are absorbed by the plant, present a small displacement from the point of deposition. Thus, it was sought to determine the impacts on the use of the organosilicone surfactant compared to the changes in the spray volumes. For that, five spray volumes and the combination of two adjuvants were compared in randomized blocks with a factorial arrangement 5×2. Reductions in volume negatively impacted the number of drops cm−2 affecting the leaf surface cover which did not exceed 13% in the lower third, in the absence of the surfactant. Also, the reduction in the volume provided decreases in the control of Asian-rust, and the use of surfactant minimized the negative impacts of the disease, reflecting on the index of the leaf area which varied up to 6.5 times on changes in the spray volume, and up to 2.8 times against the use of the surfactant in relation to the mineral oil isolated. Grain yield was negatively affected as reductions in the spray volumes, occurred with less impact when the surfactant was used. Thus, coverage of the leaf surface and the number of drops cm−2 along the plant profile respond to the addition of the surfactant and to the increase of the spray volume, having relation with the control of soybean Asian-rust, and affecting the leaf area index and productivity.